Investigating Fibroblast-Induced Collagen Gel Contraction Using a Dynamic Microscale Platform - Zhang, Tianzi; Day, John H.; Su, Xiaojing; Guadarrama, Arthur G.; Sandbo, Nathan K.; Esnault, Stephane; Denlinger, Loren C.; Berthier, Erwin; Theberge, Ashleigh B. (Frontiers in Bioengineering and Biotechnology, 2019)
Mechanical forces have long been recognized as fundamental drivers in biological processes, such as embryogenesis, tissue formation and disease regulation. The collagen gel contraction (CGC) assay has served as a classic tool in the field of mechanobiology to study cell-induced contraction of extracellular matrix (ECM), which plays an important role in inflammation and wound healing. In a conventional CGC assay, cell-laden collagen is loaded into a cell culture vessel (typically a well plate) and forms a disk-shaped gel adhering to the bottom of the vessel. The decrement in diameter or surface area of the gel is used as a parameter to quantify the degree of cell contractility. In this study, we developed a microscale CGC assay with an engineered well plate insert that uses surface tension forces to load and manipulate small volumes (14 µL) of cell-laden collagen. The system is easily operated with two pipetting steps and the microscale device moves dynamically as a result of cellular forces. We used a straightforward one-dimensional measurement as the gel contraction readout. We adapted a conventional lung fibroblast CGC assay to demonstrate the functionality of the device, observing significantly more gel contraction when human lung fibroblasts were cultured in serum-containing media versus serum-free media (p≤0.01). We further cocultured eosinophils and fibroblasts in the system, two important cellular components that lead to fibrosis in asthma, and observed that soluble factors from eosinophils significantly increase fibroblast-mediated gel contraction (p≤0.01). Our microscale CGC device provides a new method for studying downstream ECM effects of intercellular cross talk using 7-35 fold less cell-laden gel than traditional CGC assays.